Time-to-Referral, Use, and Efficacy of Cardiac Rehabilitation After Heart Transplantation. Issue 3 (March 2015) - Marzolini, Susan; Grace, Sherry L.; Brooks, Dina; Corbett, Dale; Mathur, Sunita; Bertelink, Robert; Skeffington, Valerie; Alter, David; Oh, Paul
Abstract : Background: Timely access, adherence, and efficacy of cardiac rehabilitation programs (CRP) are important given the potential to mitigate or reverse the side effects of immunosuppressive medications, weight gain, and cardiovascular deconditioning that place heart transplant (HT) recipients at increased cardiovascular risk. However, there is a dearth of information on use and efficacy of CRPs. Therefore, we examined process indicators (time to referral and correlates, program adherence) and clinical outcome indicators (functional capacity (VO2peak ), anthropometrics) of CR post-HT compared to post–coronary artery bypass graft (CABG). Methods: Baseline, 6-month exercise stress test results, and anthropometrics were examined retrospectively among consecutively enrolled post-HT and age-matched and sex-matched CABG patients. Time to referral and program entry, attendance, and completion rates were also measured. Results: Heart transplant (n=43) and CABG patients were referred 24.9±48.9 and 2.1±3.6 months, respectively, after surgery ( P =0.003). Once referred, there was no difference in elapsed-time to program entry ( P =0.2). There was a positive relationship between time to referral and baseline waist circumference (r=0.5, P =0.001), body mass index (r=0.5, P =0.002), hip circumference (r=0.4, P =0.008), and body fat percentage (r=0.4, P =0.03) in HT. Heart transplant and CABG patients had similar rates of CRP dropout (27.9% vs. 37.2% respectively, P =0.4). There was improvement in VO2peak for HT (2.4±4.2 mL/kg/min; P =0.02) and CABG (5.5±5.4 mL/kg/min, P <0.001), but was greater for CABG ( P =0.04). Anthropometric measures remained stable for both cohorts ( P >0.05). Conclusion: There is a lengthy delay in time from HT to CRP referral, though once referred, gain significant benefit in functional capacity. The appropriateness of this wait needs to be elucidated; however, it appears that longer wait times are associated with adverse effects on body composition. Abstract : Post heart transplant rehabilitation and outcomes show that rehabilitation achieves significant gains for the recipients and suggests that referral and initiation of rehabilitation should be instituted earlier.